Rebuilding the National Economy by Issuance of The First Malaysia Digital Sukuk (Sukuk Prihatin) And Its Distribution Through Fintech Services: A View from The Perspective of Maqasid Al-Shari'ah - Fisol, Wan Nazjmi bin Mohamed; Saad, Muhammad Aizat bin (The journal of contemporary issues in business and government, 2021)
The main objective of this paper is to focus on rebuilding the national economic by issuance of Sukuk Prihatin and using FinTech services for its distribution from the perspective of Maqasid Al-Shari'ah. The study using the qualitative method which based on library researches such as books, journals, articles and any other related materials. The findings of this research show the using of FinTech in the distribution of Sukuk Prihatin in rebuilding the national economy is in line with the doctrine of Maqasid Al-Shari'ah. It can be concluded that the using of FinTech services in the distribution of Sukuk Prihatin in rebuilding the national economy is in line with the doctrines of preservation of religion (deen), preservation of life (nafs), preservation of intellect (‘aql), preservation of lienage (nasl) and preservation of wealth (maal) emphasized in Maqasid Al-Shari'ah.